Project Method as a Means of Forming Research Skills of Students - qizi, Dursunova Jamila Ahmat (Research Parks Publishers, 2023)
In the context of the modernization of education, the focus of teachers is on the activities of students. What is important is not so much the end result as the process of acquiring knowledge. It is necessary to teach students to study independently, acquire knowledge, adapt to life situations, make decisions independently, and think critically. With the traditional approach and traditional teaching aids, these tasks are difficult to solve. Projective technology allows this to be done quite successfully. The article deals with the issues based on analyzing project method as a means of forming research skills of students.